Determination of N, N-diethyl-3-methylbenzamide and ethyl-butyl-acetylaminopropionate in insect repellent using near infrared spectroscopy and multivariate calibration - Vilar, Welma Thaíse Silva; Barbosa, Mayara F.; Pinto, Licarion; de Araújo, Mário César Ugulino; Pontes, Márcio José Coelho (Microchemical journal, 2020)
•NIR spectrometry and multivariate calibration used to determine active principles in insect repellent.•The method presented a high correlation with the reference HPLC-DAD.•Satisfactory prediction results were obtained for all models of DEET and IR 3535.•No systematic errors or significant differences were found. Aedes aegypti mosquitoes are vectors of diseases such as dengue, chikungunya, zika and yellow fever. With the increase in the incidence of these diseases the population has resorted to the use of repellents searching to protect themselves from mosquito attack. The Brazilian market offers a wide variety of products with different active principles in varying levels of concentration, times of action and different prices, where DEET (N, N-diethyl-3-methylbenzamide) and IR3535 (ethyl-butyl-acetylaminopropionate) based repellents are suitable for use around adults and children, respectively. The action time of these repellents depends, among other factors, on the concentration of their active ingredients. Chromatographic methods are recommended to quantify these compounds in different samples. However, these methods require long analysis time, and use reagents that are expensive and generate toxic waste. Near Infrared Spectroscopy (NIRS) has been applied in several areas of research on this subject and is characterized by its rapid, low cost, non-destructive characteristics no sample treatment is required. The present work proposes the development of a methodology based on NIR spectroscopy and multivariate calibration for determination of DEET and IR 3535 in samples from commercial repellents. A PerkinElmer FT-NIR spectrometer equipped with a 0.1 cm quartz cell was used to obtain the NIR spectra in the range of 750–2500 nm, with a resolution of 0.1 nm and an average of 16 scans. The reference analysis for the determination of DEET and IR3535 was performed using high performance liquid chromatography with diode array ultraviolet detection (HPLC-DAD). Calibration models based on partial least squares (PLS) regression across spectral bands, the same algorithm using intervals (iPLS), and multiple linear regression (MLR) with previous selected of variables by successive projections algorithm (SPA), stepwise (SW) and genetic algorithm (GA) were developed and compared. Satisfactory prediction results were obtained for all models with RMSEP values ranging from 0.70 to 1.18% (m m−1) and 0.64 to 1.12% (m m−1) for DEET and IR3535, respectively. In addition, no systematic error was observed and no significant differences were found between predicted and reference values obtained by HPLC analysis for 178 samples, according to a t-paired test at the 95% confidence level.